Cross-National analysis of students' socio-economic status on the educational achievement - Sova, Jan (2022)
This thesis examines the effect of students' socio-economic status (SES) on educational outcomes, focusing on student achievement in math, science, and reading. Data are obtained from the population of 15-year-olds in 40 European countries from The Programme for International Student Assessment (PISA). A set of items on household possessions is used to measure the SES dimensions, which are used to construct a custom Household Possessions Index. Variables capturing the occupational status of the father and mother are also used, as well as variables capturing the education level of the father and mother. This thesis confirms that the constructed Household Possessions Index can be used as an indicator of SES. The first hypothesis that students with higher SES achieve better educational outcomes is confirmed based on student performance in math, science, and reading. The second hypothesis, that differences between countries in the strength of SES effects diminish over time, cannot be confirmed because of the mixed results across countries.